Customer Satisfaction as a Mediator of Digital Marketing and Spiritual Value on Patient Loyalty - Annisa Ratnaningtyas; Martaleni Martaleni; Tri Cicik Wijayanti (LPPM STIE KRAKATAU, 2026)
This study examines the mediating role of customer satisfaction in the relationship between digital marketing, spiritual value, and patient loyalty in pesantren-based hospitals. A quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) was applied. Data were collected from 160 patients at Yasyfin Darussalam Gontor Hospital using a structured Likert-scale questionnaire. The findings show that digital marketing and spiritual values significantly influence customer satisfaction. Spiritual value directly impacts patient loyalty, whereas digital marketing influences loyalty indirectly through satisfaction. Customer satisfaction was the strongest mediator. Integrating digital marketing strategies with spiritual services enhances patient satisfaction and loyalty. Customer satisfaction plays a key role in linking these factors to the long-term loyalty of patients. This study contributes to the literature by demonstrating the combined impact of digital marketing and spiritual care on patient loyalty, highlighting the importance of addressing both technological and emotional needs in healthcare settings. This study is limited by its focus on a single hospital with a sample size of 160 patients. The cross-sectional design restricts the ability to capture changes in patient loyalty over time, and other influencing factors such as service quality were not considered.